THE IMPACT OF BRAND CREDIBILITY ON BRAND EQUITY IN THE BEAUTY INDUSTRY - Ilma Wulansari Hasdiansa (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
This research investigates the impact of brand credibility on brand equity in the beauty industry, particularly focusing on skincare products. The objective is to explore how the perceived trustworthiness and expertise of a brand influence its overall brand equity, which includes customer loyalty, brand awareness, perceived quality, and brand associations. Using a quantitative approach, data were collected through surveys distributed to 45 consumers who are regular users of beauty products. Statistical analysis, including regression analysis, was used to examine the relationship between brand credibility (comprising trustworthiness and expertise) and brand equity. The results show that brand credibility has a significant positive effect on brand equity, with trustworthiness emerging as the stronger predictor of brand equity compared to expertise. These findings suggest that brands in the beauty industry can enhance their market position by improving their credibility, particularly in terms of trustworthiness. The research concludes that building a trustworthy brand image is essential for strengthening brand equity and sustaining consumer loyalty in a competitive market.